การผลิตไคโตโอลิโกแซ็กคาไรด์โดยวิธีทางเอนไซม์และสมบัติต้านจุลินทรีย์ และต้านออกซิเดชัน - ทิพวิมล โพธิเวส (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Different degree of deacetylation (DD) of chitosans were deacetylated by using strong alkaline and different DD of chitosan films were prepared and investigated for their properties. Moreover, chitooligosaccharides were produced from 2 different DD of chitosans (80 and 90%). The chitosans were hydrolysed by 3 commercial enzymes including papain, cellulase and lysozyme for 1 to 16 hours. Next step, properties of antimicrobial and antioxidation of different molecular weight of chitooligosaccharides (41.14, 14.28 and 5.06 kDa) were investigated. Chitin was deacetylated by boiling (950C) in concentrated sodium hydroxide (50%) solution for 120-300 minutes. The DD of chitosan was determined by potentiometric titration method. Chitin possessed the DD at 7.74%. The alkaline deacetylation produced chitosan with DD of 15.24-70.19%. The linear relationship between DD and deacetylation time was found (DD = 2.476 + 0.230t, R2 = 0.915). The deacetylation time had no effect on yield and whiteness of the obtained chitosans. The film from the obtained chitosan at each deacetylation time were formed and investigated for their properties. The results show that tensile strength, elongation and water vapor transmission rate of the films were increased by increasing the deacetylation time. Molecular weight of chitooligosaccharides was determined by viscometric method. After 16 hours of enzyme hydrolysis, it was found that chitooligosacccharides produced by DD 90% of chitosan and hydrolyzed by papain produced the lowest molecular weight chitooligosaccharides (5.06 kDa). Solubility of chitooligosaccharide was increased with decreasing molecular weight of samples. Furthermore, the lower molecular weight chitooligosaccharides possessed the higher antioxidant activities (DPPH, reducing power and chelating ability) than the higher molecular weight chitooligosaccharides (41.14 and 14.28 kDa) and chitosan. To determine antimicrobial activity of chitooligosaccharide, the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) measurement, chitooligosaccharide possessed higher in antimicrobial than chitosan. MIC of all chitooligosaccharide samples were in the rage of 16 – 64 µg/ml for tested bacteria including Escherichia coli, Staphylococcus aureus, Salmonella Typhimurium and Salmonella Enteritidis. While, the MIC of chitosan was >64 µg/ml in all tested bacteria. Moreover, all chitooligosaccharide samples can kill E. coli with concentration of 64 µg/ml (MBC). However, the higher concentration of chitooligosaccharide was requested to kill the other tested bacteria.